Framing Detik Jatim.com Dalam Pemberitaan Wisata Heritage Surabaya Periode Juli – Desember 2024 - Angely Rahma; M. Rifa'i (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the framing of heritage tourism news in the online media DetikJatim.com during the period of July to December 2024. The research uses a qualitative method with Robert N. Entman’s framing analysis approach, which includes four elements: define problem, diagnose causes, make moral judgment, and treatment recommendation. A total of 28 news articles were analyzed and classified into six categories of heritage tourism. The findings show that DetikJatim frames the main issue as the lack of historical preservation and the weakening of the meaning of heritage areas amid modernization. The highlighted causes include weak historical literacy, dominance of folk narratives without academic support, and the repurposing of historical spaces. Morally, the media views historical preservation and the strengthening of local identity as a collective responsibility, encouraging the public to understand and appreciate history. The suggested solutions include reintroducing historical knowledge, educating through narratives of struggle, revitalizing sites, or simply highlighting their existence